Effects of experimentally induced self-affirmation on the openness to meat reduction and alternative protein sources - Branković, Marija; Budžak, Anastasija; Tulić, Nađa; Janković, Jovana (Frontiers in Psychology, 2023)
Introduction Consumption of animals entails disregarding the pain of sentient beings, and acknowledging this can threaten an individual’s image of oneself as a moral person. Also, abstaining from meat in a meat-eating culture can threaten an individual’s valued group identity. Previous research on inter-group relations suggests that self-affirmation, affirmation of personally or collectively important values, can help individuals alleviate self-threats since it enhances one’s global self-image and decreases threat perceptions. Methods We tested for potential effects of self-affirmation on openness toward reducing meat consumption in an experimental study. Participants (N = 277) were randomized into an individual affirmation, group affirmation, or a control condition. Individual affirmation participants ranked a list of values and then wrote a short paragraph about their first-ranked value. Group affirmation participants did a similar task, focusing on the values of their ethnic group, while participants in the control condition had an unrelated task of ranking their color preferences. Participants then read a persuasive message presenting health risks related to meat consumption and the health benefits of reducing meat. Finally, they indicated their openness toward reducing meat consumption and acceptability of plant-based alternatives and lab-grown meat. Results and Discussion Results show that affirmed participants expressed more readiness to reconsider their meat consumption habits, reduced perceptions of vegetarianism as a threat to the local culture, and more positive perceptions of the idea of lab-grown meat. However, self-esteem and frequency of meat consumption pose important limitations to the experimental effects. We discuss the findings from the perspective of self-and collective identity threats and the potential of self-affirmations to create a more open debate about animal product consumption.